PENGARUH KEBIJAKAN MONETER TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Jul Fahmi Salim (JURNAL EKOMBIS, 2018)
This study aims to analyze the influence of monetary policy on economic growth in Indonesia. This study uses secondary data in quarterly form from 2010q1 to 2016q3. To achieve the research objectives, data analysis used multiple linear regression. From the research results found that monetary policy is effective in improving economic growth of Indonesia. Where the exchange rate has a positive and significant effect, while inflation has a negative and significant effect on economic growth. This means the government must be able to maintain the stability of the exchange rate and keep the inflation rate so that economic growth can be in a positive trend.Keyword : Monetary Policy, Exchange Rate, Inflation, Economic Growth